Some issues of the General Part of the Criminal Code of the Republic of Belarus of 1999 in the view of the principle of guilty responsibility - Gruntov, Igor O. (Journal of the Belarusian State University. Law, 2019)
Criminal Сode is a kind of historical document, through which, as in the mirror, one can see the system of social values in the given period of the society and the state; the effectiveness and equivalence of legal measures used to regulate and protect the most important social relations. The current Criminal Code of the Republic of Belarus of 1999 replaced the Criminal Code of BSSR of 1960 to regulate and protect the socio-economic relations of the new independent state. But time moves on. It has been almost twenty years since the Criminal Code of the Republic of Belarus of 1999 was adopted and came into effect. Massive historical changes of an economic, social and political nature have taken place in our fatherland in this period. The world has changed and we have changed over these decades. The state and society try to respond in a timely and equivalent manner to socially dangerous challenges and changes in reality, applying measures of an economic, social, and including criminal law nature. More than one and five hundred thousand norms and legal institutions of the Criminal Code of the Republic of Belarus have been amended and supplemented. These phenomena can be explained by objective processes occurring in the surrounding world. At the same time, it should be noted that not all changes can be explained only by the desire of the legislator to respond to unexpected socially dangerous external challenges. The twenty-year application of the Criminal Code of the Republic of Belarus indicates that certain errors in the design of legal norms were made at the time of the adoption of the Criminal Code of the Republic of Belarus of 1999, but they were not noticed and eliminated in the initial period of time, or in subsequent years. This is most typical for some norms of the General Part of the Criminal Code. It is especially noticeable if we analyze the constructions of such norms in the light of the principle of guilty responsibility standards.